Electron Spin Resonance of an Irradiated Single Crystal of 5-Chlorouridine - Reiss, Keith W. (1971)
Electron spin resonance signals from radicals of different types have been observed in γ-irradiated 5-chlorouridine. The strongest absorption, a broad resonance with g values ranging from 2.2 to 3.0, must arise from spin density concentrated on chlorine, probably from trapped atoms. However, hyperfine structure expected from Cl nuclei could not be resolved, evidently because of the low symmetry and diversity of the trapping sites and the large anisotropy in the nuclear coupling and g tensor. A very much weaker resonance, which in the single crystal has a resolvable hyperfine structure, was found to be similar to that observed in normal uridine subjected to thermal H atoms. It is concluded that an H atom, probably released by irradiation from the ribose group, replaces the Cl atom on the basic ring to form normal uridine, and that a second H atom later adds to the uridine to form the observed H-addition radical. The differences in the electron spin resonance constants of this radical from those of uridine bombarded with H can be attributed to the proximity of the trapped Cl atoms and to differences in the crystal structure of the chlorouridine from that of normal uridine.